Steps to a new edition of the Hebrew Bible - Hendel, Ronald S. (Atlanta : SBL Press, 2016)
"Our understanding of the textual history of the Hebrew Bible has been transformed in the wake of the discovery of the Dead Sea Scrolls. Hendel explores and refines this new knowledge and formulates a rationale for a new edition of the Hebrew Bible. The chapters situate The Hebrew Bible: A Critical Edition project in a broad historical context, from the beginnings of textual criticism in late antiquity and the Renaissance to the controversies in contemporary theory and practice. This book combines close analysis with broad synthesis, yielding new perspectives on the text of the Hebrew Bible"--
1. Prologue to the Hebrew Bible: a critical edition (HBCE) -- 2. A response to criticisms -- 3. The idea of a critical edition of the Hebrew Bible: a genealogy -- 4. What is a biblical book? -- 5. The epistemology of textual criticism -- 6. A typology of scribal error -- 7. Assessing the text-critical theories of the Hebrew Bible after Qumran -- 8. The (proto- ) Masoretic text of the Pentateuch -- 9. Problems of classification and other texts of the Pentateuch -- 10. The contribution of Frank Cross to textual criticism, with special attention to 4QSama -- 11. The dream of a perfect text: textual criticism and theology in early modern Europe -- 12. The untimeliness of biblical philology -- 13. From polyglot to hypertext -- Appendix: Comparing critical editions: BHQ Proverbs and HBCE Proverbs.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Bible. -- Criticism, Textual; Bible; RELIGION / Biblical Studies / Old Testament; RELIGION / Judaism / Sacred Writings; Criticism, interpretation, etc; Electronic books